Cascading Effects of Cumulative Trauma: Callous Traits among Justice Involved Youth. (October 2022) - Yoder, Jamie; Tunstall, Ashley
Youth involved in the juvenile justice system (JJS) have high rates of trauma relative to youth in the general population. Criminological research has posited that callous traits are some of the most prominent risk factors associated with onset and recidivistic criminal behavior. It stands to reason that research should test intermediary variables explaining the connection between cumulative trauma and risks for criminal behavior to better isolate trauma-driven determinants of callous traits. This study employs a structural equation model to test the connections between cumulative trauma, trauma symptoms, behavioral regulation, and callous traits among a sample of JJS involved youth ( N = 336). Results revealed there was not a direct relationship between cumulative trauma and callous traits, but there were mediated effects of the variables in portions of the model; the developmental risks resulting from cumulative trauma, specifically trauma symptoms and behavioral regulation increase the likelihood for callous traits. Implications are discussed.